Household food insecurity and unimproved toilet facilities associate with child morbidity: evidence from a cross-sectional study in Bangladesh - Mohammad Ashraful Islam; Mahfuzur Rahman; Md. Fakhar Uddin; Md. Tariqujjaman; Gobinda Karmakar; Mohammad Ashikur Rahman; Matthew Kelly; Darren Gray; Tahmeed Ahmed; Haribondhu Sarma (BMC, 2022)
Abstract Background Despite recent progress in rural economic development and food production, the prevalence of household food insecurity (FI) and use of unimproved toilet facilities are widespread in Bangladesh. Evidence regarding the consequencs of household FI and poor sanitation on child morbidity is scarce. This study aimed to understand the association of FI and unimproved toilet facility with morbidity status of under-5 children in Bangladesh. Methods We used data from a cross-sectional survey that was conducted as part of an evaluation of the Maternal, Infant and Young Child Nutrition (MIYCN) Program in 9 districts of Bangladesh. The study population included children aged 6-59 months and their caregivers, identified using a two-stage cluster-sampling procedure. Child morbidity status was the outcome variable, and household FI status and type of toilet used were considered the main exposure variables in this study. We performed logistic regression, calculated adjusted odds ratios (AOR) to assess the association of child morbidity with household FI and unimproved toilet facility after adjusting for potential confounders. Results A total of 1,728 households were eligible for this analysis. About 23% of the households were food-insecure, and a large number of households had improved toilet facilities (93.4%). In the multivariable logistic regression model, we found that children in food-insecure households with unimproved toilet facility had 5.88 (AOR: 5.88; 95% CI 2.52, 13.70) times more chance, of being morbid compared to the children of food-secure households with improved toilet facility. A similar association of FI and toilet facilities with each of the morbidity components was observed, including diarrhea (AOR:3.6; 95% CI 1.79, 7.89), fever (AOR:3.47; 95% CI 1.72, 6.99), difficult or fast breathing with cough (AOR:3.88; 95% CI 1.99, 7.59), and difficult or fast breathing with blocked or running nose (AOR:1.29; 95% CI 0.56, 2.95). Conclusions Our study shows that household FI and unimproved toilet facility jointly have more deteriorative effects on child morbidity than either of these conditions alone. Therefore, it is recommended to consider these two critical factors while designing a public health intervention for reducing morbidity among under-five children.